Perspektif KH. Imam Zarkasyi Terhadap Modernisasi Pesantren - Billah Wahid Asa (Tasamuh: Jurnal Studi Islam, 2023)
This paper aims to elaborate the thoughts and practices of Imam Zarkasyi in modernizing traditional Islamic education called Pesantren. The methods used in this study are descriptive and explanatory research. Data is collected from documents such as books, research articles and brochures, as well as from the author's observations over time. This paper identifies that Imam Zarkasyi's educational thoughts and experiences as well as his religious inclinations played an important role in the modernization of his boarding school. This research also found that Imam Zarkasyi's thoughts and practices in modernizing the pesantren system originated from his serious observation and evaluation and his appreciation of the traditional pesantren and madrasah education system. The step taken by Imam Zarkasyi to modernize the education system is to integrate the pesantren and madrasah systems.